Publishing a blog with Blogger : Visual QuickProject guide. - Castro, Elizabeth. 4 0 16; 5 (Berkeley, CA : Peachpit Press, 2005)
Presents a step-by-step visual guide to creating and maintaining a Weblog on the Internet.
Includes index.
Keywords: 2 -- 0; 6; Blogger;Blogger -- Handbooks, manuals, etc.;Handbooks, manuals, etc; Computer programs;Computer programs;Computer software;Computer software -- Blogs;Internet;Blogs;Internet -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2